Obesity in youth : causes, consequences, and cures - Heinberg, Leslie J.; Thompson, J. Kevin (American Psychological Association, 2009)
"Rates of obesity in youth have tripled in the past 20 years. Today it is estimated that more than 20% of American children and adolescents are overweight. This emerging epidemic has stimulated a great deal of new research into the formative influences and the interpersonal, social, and psychological effects of obesity on children. In this thorough and incisive book, editors Leslie J. Heinberg and J. Kevin Thompson have gathered an august group of researchers to describe these trends and to discuss their implications for the assessment, treatment, and prevention of obesity in youth. The book opens by acquainting readers with key genetic influences and dietary patterns. Later chapters on treatment and prevention are written from medical and public health perspectives, but contributors focus primarily on psychological aspects of obesity such as teasing, body image, and comorbidity with mental disorders as well as the psychosocial consequences for children, families, and the larger society. This wide-ranging volume will be of great use for public and mental health professionals as well as academics and researchers who seek a fuller understanding of the fight against childhood obesity"--Jacket. (PsycINFO Database Record (c) 2009 APA, all rights reserved)